Tradición, revuelta y conciencia de clase Estudios sobre la crisis de la sociedad pre industrial - Vizcardo Otazo, Daniel (2010)
Tradición, revuelta y conciencia de clase Estudios sobre la crisis de la sociedad pre industrial